2019
DOI: 10.3389/fpls.2019.01544
|View full text |Cite
|
Sign up to set email alerts
|

It Is Feasible to Produce Olive Oil in Temperate Humid Climate Regions

Abstract: Worldwide olive industry has expanded into new climatic regions outside the Mediterranean basin due to an increase in extra virgin olive oil demand posing new challenges. This is the case of Uruguay, South America, where the olive crop area reached 10,000 hectares in the last 15 years and is intended to the production of EVOO. Uruguay has a temperate humid climate with mean precipitations above 1,100 mm per year but unequally distributed, mild winters, and warm summers, with mean annual temperatures of 17.7°C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
2
8
0
1
Order By: Relevance
“…Despite the fact the levels found in both seasons are different, they are in concordance with previously reported oils from similar experiments [18,46,51]. In humid climate conditions, the differences between two growing seasons could affect not only the oil content [58] but also the minor oil components, such as phenolic compounds and the fatty acid profile.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the fact the levels found in both seasons are different, they are in concordance with previously reported oils from similar experiments [18,46,51]. In humid climate conditions, the differences between two growing seasons could affect not only the oil content [58] but also the minor oil components, such as phenolic compounds and the fatty acid profile.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between fruit production and ETc was shown to be curvilinear by Moriana et al [10], which means that high production could be reached at lower values than those of the maximum potential ETc. It was demonstrated that under full irrigation olives can achieve high yields (8 t/ha/year) in humid template regions [58]. In our study, if we compare WP (estimated according to kg/tree based on the applied water) between both irrigation treatments, we observe that it was always higher in the 50% ETc treatment than in the 100% ETc one, since yields in kg/tree were similar between both and the water applied was half in the 50% ETc one.…”
Section: Discussionmentioning
confidence: 99%
“…For the environmental conditions, olive is considered one of the most suitable and best adapted species to the Mediterranean-type climate, characterized by mild and humid winters, with minimum temperatures of about −4 °C, and hot and dry summers, with maximum temperatures of about 50 °C; and most of the rainfalls concentrated in the cold season. [ 16 , 18 , 19 , 20 ]. Under the climate conditions of Mediterranean region, the vegetative-reproductive cycle is biennial in which production and induction of flower buds coexist at the same time, on the growing shoot, for fruiting the following year [ 13 , 21 , 22 , 23 , 24 , 25 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fruit maturity index was determined considering the skin and mesocarp color: 0, intense green skin; 1, yellow green skin; 2, reddish or purple skin in less than half of the fruit; 3, reddish or purple skin in more than half of the fruit; 4, black skin and white mesocarp; 5, black skin and mesocarp turning to purple immediately under the skin; 6, black skin and mesocarp only purple colored up the middle of the fruit; and 7, black skin and totally purple mesocarp. The index, developed by Uceda and Frías in 1975, was obtained by analyzing 100 fruits and weighting the proportion of each maturity stage. , The fruits in the early stage (ES: MI = 1) were collected in April (southern hemisphere) and those in the intermediate stage (IS: MI = 2.5) were collected in May (Figure ).…”
Section: Methodsmentioning
confidence: 99%